The Impact of Cryptocurrency Adoption on Personal Financial Management Strategies Among Generation Z - Slamet Abdul Muslikh; Adiba Fuad Syamlan; Anisaul Hasanah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study explores the impact of cryptocurrency adoption on personal financial management (PFM) strategies among Generation Z. As digital natives, Generation Z is increasingly integrating cryptocurrencies into their financial routines, yet their financial literacy levels vary significantly. Employing a qualitative literature review methodology, this research analyzes recent academic publications to examine how generational characteristics such as digital fluency, risk tolerance, and social media influence moderate the relationship between crypto usage and financial behaviors like budgeting, saving, and debt management. The findings reveal a dual effect: while cryptocurrency can enhance financial autonomy and portfolio diversification, it also increases the risk of impulsive and speculative behaviors among less financially literate users. This research underscores the importance of developing targeted financial education programs that incorporate both digital and behavioral components. The study contributes theoretically to behavioral finance and innovation diffusion models, and offers practical recommendations for educators and policymakers seeking to improve financial outcomes for Generation Z in a rapidly evolving digital economy.